Case report: Immunotherapy plus chemotherapy and stereotactic ablative radiotherapy (ICSABR): a novel treatment combination for Epstein-Barr virus-associated lymphoepithelioma-like intrahepatic cholangiocarcinoma - Li, Ruizhen; Cheng, Ke; Li, Xiaofen; Chang, Chen; Lv, Wanrui; Xiaoying, Li; Zhang, Pei; Yang, Heqi; Cao, Dan (Frontiers in Pharmacology, 2023)
Epstein-Barr virus-associated lymphoepithelioma-like intrahepatic cholangiocarcinoma (EBVa LEL-ICC) is a rare tumor, characterized by a rich tumor immune microenvironment (TIME). While this tumor is reportedly sensitive to immunotherapy, its response has been inconsistent. This decreased sensitivity was associated with reduced TIME abundance. We report the case of a 53-year-old woman with EBVa LEL-ICC having reduced TIME abundance. The patient presented with a liver lesion, which was detected using ultrasound. Initially, the tumor was sensitive to immunotherapy and chemotherapy (IC), but resistance developed after a short interval. Subsequently, stereotactic ablative radiotherapy (SABR) was added to the patient’s treatment, which now consisted of ICSABR. Successful tumor shrinkage was achieved with the combination therapy regimen. Thus, surgery and ICSABR are effective adjuncts to the first-line IC therapy in improving the survival rate of patients with EBVa LEL-ICC. The results of this study support multidisciplinary treatment as a viable treatment strategy for EBVa LEL-ICC.